2019
DOI: 10.21272/mmi.2019.2-10
|View full text |Cite
|
Sign up to set email alerts
|

Innovative sharing economy’s business models in tourism: case of Airbnb in Prague

Abstract: This paper sums up one of issues in tourism industry within scientific framework by analysing the relationship between average daily rate and occupation rate of rentals in a sharing economy platform. The main aim of the current research is to verify the existence of a dependency between the property type and the occupancy rate, and, identify if the specific property type is more demanded on the market and confirm or reject an existence of the dependency between an average daily rate and the occupancy rate. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Our contribution reflects on these facts and solves the problem of looking for methods to create optimal decision-making mechanisms in the financing process of start-ups sector-oriented in the field of air transport with the aim of ensuring their financing security. There are several funding support models at present, the pressures for innovative development and the exploitation of the country’s innovation potential that create new forms, but a deeper analysis of funding processes with complementary risk or safety assessments are absent so far [5,6,7]. The main problem is their considerable methodological difficulty and dependence on expert evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Our contribution reflects on these facts and solves the problem of looking for methods to create optimal decision-making mechanisms in the financing process of start-ups sector-oriented in the field of air transport with the aim of ensuring their financing security. There are several funding support models at present, the pressures for innovative development and the exploitation of the country’s innovation potential that create new forms, but a deeper analysis of funding processes with complementary risk or safety assessments are absent so far [5,6,7]. The main problem is their considerable methodological difficulty and dependence on expert evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…It can be a social and cultural contact between the local population and visitors; awareness of the value of the heritage and the need to preserve it will increase both among visitors and the local population; the sense of identity and unity of the local community will be strengthened; local transport, other services will be more fully used, and therefore their viability will increase. That is why tourism in its best form can help rural communities find new opportunities for local economic development, improve their quality of life, preserve heritage and social values [6].…”
Section: The Development Of Rural Tourism As a Factor Of Rural Areas` Imagementioning
confidence: 99%
“…The tourism industry is one of the fastest-growing industries in the world (Ranasinghe, 2019). The rapid growth of digital technology, intensive presence on social media platforms leads to the emergence of online content sharing (people to people), that results in the emergence of sharing economy (Krajcik, Kljucnikov, and Rihova, 2019). Regarding the ridesharing industry Ključnikov, Popesko, and Kloudová, (2019) concluded that real-time ridesharing services dramatically lower the cost of transportation and argued that low digital literacy of the users and providers can make such services infeasible and disadvantageous.…”
Section: Introductionmentioning
confidence: 99%